Takwil Al-Qur'an Syi'ah Isma'iliyah: Studi Penakwilan pada Kisah Nabi Isa As - Dzikrillah Alfani, Ilzam Hubby (Jurnal Penelitian Ilmu Ushuluddin, 2023)
This research is about the Shia Sect. The development of Shia is divided into three, including: Itsna 'Asyariyah, Isma'iliyah and Zaidiyah. Shia Isma'iliyah is the second largest sect. The development of Shia is very rapid but requires a long and complex time. The interpretation that is very popular among the Shia is the Tafsir Asas al-Ta'wil. The purpose of this research is to popularize the rarely known Shia interpretation. This research provides an overview of the Ismaili Shia figures, the meaning of ta'wil and the difference with the term tafsir. Then, covered with examples of interpretation of the story of Prophet Isa As. This type of research is classified as qualitative by relying on written data. The result of this research and discussion is that the book Tafsir Asas al-Ta'wil by al-Nu'man ibn Hayyun is the basic basis of mysticism philosophy as an understanding of a nature contained in the Al-Qur'an. It is divided into six sections which interpret the stories of the prophets in the Al-Qur'an, including: Prophet Adam, Prophet Noah, Prophet Abraham, Prophet Musa, Prophet Isa, and Prophet Muhammad SAW. The concept of ta'wil according to Syi'ah Isma'iliyah is an attempt to find the inner meaning or sign, essence, and truth (meaning) that is hidden behind the lafadz. There are many shortcomings in this research. Therefore, Drivers of Islamic Studies are expected to continue to deepen research related to the Ismaili Shia Theme.